Macro-scale designs through topological deformations in the built environment. (June 2017) - Agirbas, Asli; Ardaman, Emel
Design studies are being done on contemporary master-plans which may be applied in many locations worldwide. Advances in information technology are becoming the base model of design studies, and these may be more effective than the efforts of humans in the field of architecture and urban design. However, urban morphology variables and constants must be considered while designing contemporary master-plans in the existing built environment. The aims of this study were to extend the use of computer software for different applications and to make a topological work in the regional context. Accordingly, a case study was made using the nCloth simulation tools to create non-Euclidean forms while protecting the road system, which is one of the constant parameters of urban morphology in the built environment.